O‘ZBEKISTON MINTAQALARIDA QISHLOQ XO‘JALIGINI RIVOJLANTIRISH YO‘NALISHLARI (UBS Scientific Bulletin, 2025)
The economic activity of farmers of the Republic of Uzbekistanwas selected as the object of the study. In the context of structural transformationand diversification of the economy, it consists in the development of scientificproposals and practical recommendations on improving the economic mechanismof agricultural development in the regions of Uzbekistan, improving theeffectiveness of the management mechanism.